Longevitiness- Individual’s Holistic Management Via Manache Shlok - Preeti Mulay, Swati Kadlag, Neha Divekar (International Journal of Modern Agriculture, 2020)
Remodeling the structure of your brain is possible by having the aware of senses, mind, thoughts, emotions etc. In today’s world bridging the gap between technology, science, religion and spirituality is the essence of good life. Acceptance of individuals, situations, events, nature, problems etc. will truly come into action only when belongingness will arise and stay, about home, office, work, health, etc. to name a few. The ability to be fully present in the moment — can have numerous benefits, everything from decreased stress and sadness to increased levels focus and happiness, according to general mindfulness research. To maintain the happy state of mind always, enthusiasm plays an important role, which encourages and gets the regular physical activities done, with variations to reach to all cells in body. To be the leading player of this GAME (Good-life, Acceptance, Mind and Enthusiasm) Manache Shlok by Shree Ramdas Swamiji is the panacea. In this paper, individual’s holistic management skills via Manache Shlok is given in most easiest form.